Comparative analysis of Christians Preferences for Pentecostal and Roman Catholic Radio Stations: A study of Key FM and Radio Maria in Songea, Tanzania - Stanley Mgeni; Kaanaeli Kaale (Technium Social Sciences Journal, 2026)
This study examined Christian preferences for Key FM and Radio Maria. The investigation focused on the daily programmes aired between September and November 2023. This study employed a mixed-methods research approach based on quantitative and qualitative methods to investigate four specific objectives which are; to determine how much Christians in Songea listened to Key FM and Radio Maria FM, evaluate the content that Songea Christians prefer most from Key and Radio Maria FM, examine the reasons for Christians’ preferences for Key FM or Radio Maria FM, and determine the influence of the preferred station on Songea Christians’ faith and socio-cultural change. The study involved 110 Christians from three denominations, including Catholics, Protestants, and Pentecostals, from four wards in Songea District. The cluster sample approach allowed for a diverse group of (Christians, enhancing the study’s depth. Wimmer & Dominick (2014) say that cluster probability sampling allows researchers to get a sample that correctly reflects the numerical distribution of diverse subgroups within the population. Purposive sampling was used to identify four key informants from Catholic and Protestant denominations, providing comprehensive knowledge on marketing practices related to Christian radio stations. This method was both affordable and effective. The research used questionnaire to obtain information from Christians and interviews to gather primary data to get information from religious leaders. Young adults spent 1-2 hours, adult 3-5 hours, the elderly spent more than 10 hours. The study indicates that Songea Christian prefers Radio Maria religious programmes, while most prefer Key FM News, Sports, and non-religious entertainment programmes.